Restoration of Load-Bearing Structures of Buildings after Accidents - O. A. Simakov (Железобетонные конструкции)
The issues of protecting buildings from special, usually non-design, impacts, including progressive collapse as a result of emergency impacts, are the subject of many scientific works and regulatory documents have been developed regulating calculation and design provisions for application at the design stage. At the same time, the issues of strengthening existing buildings and structures at the stages of major repairs, reconstruction (if measures, for example, for protection against progressive collapse were not envisaged at the design stage, then bringing the structures to the requirements of the standards is a complex, often impossible task), as well as restoration of load-bearing structures after emergency situations remain open. In accordance with the current regulatory documents, the calculation for a special limit state is carried out with reduced coefficients for loads and taking into account the dynamic hardening for the design resistance of materials. After an emergency impact, it is necessary to perform a calculation for limit states taking into account all reliability factors, which usually leads to a deficit in the bearing capacity of a significant number of load-bearing structures taking into account the damage to individual structures and the redistribution of forces to others that are not damaged. It is for this operational stage after the special impacts considered in this article that there are no special requirements and assumptions in the operation of the building’s load-bearing structures.